Analysis of the Contribution of Islamic Social Capital to Increasing MSMEs - Isna Khairani; Imsar; Nasution, Muhammad Lathief Ilhamy (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
MSMEs often face various problems that hinder their business growth. MSMEs run by students from the Faculty of Economics and Islamic Business, North Sumatra State Islamic University (FEBI UINSU) experience limited capital, limited market access and a lack of managerial knowledge. Islamic social capital, which consists of trust (X1), norms (X2), networks (X3), and religiosity (X4), can play an important role in overcoming these challenges. This research aims to discuss the contribution of Islamic social capital to improving MSMEs run by FEBI UINSU students. The method used is multiple linear regression with a questionnaire survey as a data collection instrument. The research sample is students who actively manage MSMEs on the FEBI UINSU campus. The results of data analysis show that Islamic social capital has a significant positive influence on increasing UMKM FEBI UINSU students. These findings show that Islamic social capital plays an important role in building networks, improving service quality, and supporting the growth of MSMEs. This research is expected to provide practical implications in helping students understand the importance of utilizing Islamic social capital to improve the performance and sustainability of their businesses, as well as providing theoretical implications that can enrich understanding of the role of social capital in the context of Islamic economics.